On the Integration of Scientic Information Resources of a Memory Institutes - N. E. Kalenov (Informaciâ i Innovacii)
The article deals with the issues related to the creation of an integrated information system that re-ects the scientic resources stored in “memory institu-tions” (libraries, archives and museums). The analysis of data formats in automated systems of such institutions is carried out. In contrast to the traditional approaches to the integration of memory institutions resources which are being used both abroad and in Russia, im-plemented in the form of documentary information retrieval systems (IPS), in this work, such systems are proposed to build as factographic IPS, wich are based on object-oriented approach. Such systems should contain metadata not only about the documents, but also about the objects with which they are associated, indicating the type of relationships between objects.Three kinds of relationships- “intellectual”, “informa-tion”, and “technological” are proposed. This article dis-cusses examples of establishing relationships of various kinds between such objects as a publication, person, organization, Museum exhibits, archival document and event